The housing of the people, with special reference to Dublin - Dawson, Charles (Statistical and Social Inquiry Society of Ireland, 1906)
There is no necessity to apologize for introducing this subject to the notice of the Society. It fills 'the public mind almost beyond any other domestic question. We know, from recent utterances, 'that it occupies the attention of statesmen, and even the King, who acted on the Royal Commission in 1885, has, since his accession to the throne, more than once introduced the subject into his speeches. It is, therefore, quite clear from this that, notwithstanding what has been done by legislation, by local bodies, by philanthropy and commercial enterprise, the solution of the question of the housing of the people has not, as yet, been arrived at. I do not use the word working classes, I prefer the term used by Sir Sydney Waterlow, "The Weekly Wage Classes." With few exceptions the most of us are workers, but the difficulty of finding suitable house accommodation, though there is sometimes some difficulty, is not so great with us as with those who are at physical work all day, or looking for it, whose pay is weekly, in many cases small and frequently precarious, and who have neither time nor money to fight their own battle. In fact, in this matter they are helpless.
Read Wednesday, 27th March, 1901
Keywords: Tenement buildings; Poverty; Dublin; 314.15